SEBUAH KAJIAN TENTANG KUALITAS PELAYANAN : (Studi Pada CV. Medal Karya Sumedang) - Deni Istiono. MM (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
Abstract This study aims to identify, analyze and explain the quality of services available at CV. Sumedang's Medal. This research is a descriptive study using a qualitative approach. The data collection technique is done by using observation, interview and documentation. The data analysis technique used interactive models. Checking the validity of the data was carried out by triangulating the source. From the research results show that the responses given by the CV. Medal Karya against complaints is served well even though it has to go through several processes where customer complaints must be reported to the Disturbance Office all of this is done so that customer comfort and satisfaction can be properly fulfilled. The service quality of a company is determined by the company's ability to meet the needs and desires of customers in accordance with customer expectations. So it can be seen from the dimension of service quality Reliability (Reliability) is the ability to provide the promised service immediately and satisfactorily, Responsiveness (Responsivenes) how the company responds in the service process to customers, Assurance where the company is able to instill a sense of confidence in customers, Empathy (Emphaty) sincere attention is given by the company by trying to understand customer desires, physical evidence (tangible) of ability that is seen directly in serving customers. The value of service quality depends on the ability of the company and its staff to consistently meet customer expectations.